2017
DOI: 10.1159/000478986
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive Effects of Isosakuranetin in a Rat Model of Peripheral Neuropathy

Abstract: Chronic pain remains a challenging clinical reality, yet currently available analgesics are insufficient to meet clinical needs. Increasing attention has been paid to bioactive compounds from natural plants, which may be efficacious against pain. This study examined the antinociceptive effects of isosakuranetin, a plant-derived transient receptor potential melastatin 3 blocker, in a rat model of peripheral neuropathy. Adult male Sprague-Dawley rats were first allowed to go through the chronic constriction inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…In recent years, research in rodents has revealed that the cation channel TRPM3 plays a central role in the somatosensory pathway, where it is involved in acute noxious heat sensing and in the development of inflammatory hyperalgesia (Behrendt, ; Vriens et al, ). Moreover, pharmacological inhibition of TRPM3 alleviates pain in a variety of preclinical models in mice and rats (Jia et al, ; Krugel et al, ; Straub et al, ), highlighting the potential of TRPM3 as a target for novel analgesic drugs (Held, Voets, & Vriens, ). However, whether TRPM3 is implicated in somatosensation and pain in humans remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, research in rodents has revealed that the cation channel TRPM3 plays a central role in the somatosensory pathway, where it is involved in acute noxious heat sensing and in the development of inflammatory hyperalgesia (Behrendt, ; Vriens et al, ). Moreover, pharmacological inhibition of TRPM3 alleviates pain in a variety of preclinical models in mice and rats (Jia et al, ; Krugel et al, ; Straub et al, ), highlighting the potential of TRPM3 as a target for novel analgesic drugs (Held, Voets, & Vriens, ). However, whether TRPM3 is implicated in somatosensation and pain in humans remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In mouse, TRPM3 is expressed in approximately 60% of somatosensory neurons and plays a central role in the detection of noxious heat (Vriens et al, ). Strikingly, TRPM3 −/− mice do not develop inflammatory hyperalgesia in response to injection of complete Freud's adjuvant (Vriens et al, ) and systemic TRPM3 antagonists were shown to alleviate mechanical and thermal hyperalgesia in mouse and rat models of inflammatory and neuropathic pain (Chen, Chen, Qian, Fang, & Zhu, ; Jia, Zhang, & Yu, ; Krugel, Straub, Beckmann, & Schaefer, ). Moreover, TRPM3 activity in sensory neurons is strongly suppressed by μ‐opioid receptor activation in sensory neurons, suggesting that TRPM3 may contribute to peripheral analgesic effects of opioids (Dembla et al, ; Quallo, Alkhatib, Gentry, Andersson, & Bevan, ; Yudin & Rohacs, ).…”
Section: Introductionmentioning
confidence: 99%
“…Raised oxidative stress, increased vascular permeability and release of different inflammatory mediators including substance P and calcitonin gene related peptide produced by nociceptive terminals, formation and/or release of bradykinin, prostaglandins, growth factors and cytokines leads to the occurrence of neuropathic pain 7 . Recently, the anti-inflammatory and antioxidant agents like N-acetyl carnitine and alpha lipoic acid are being investigated as add-on medications for the management of neuropathic pain 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Evidence based surveys have revealed that patients with chronic pain prefer to use herbal treatments for these painful conditions 11 , 12 . Several pre-clinical and clinical studies have reported the beneficial effect of medicinal plants in the therapy of painful neuropathy 4 , 8 , 13 17 . Toxicodendron pubescens P. Mill belonging to family anacardiaceae is known as Rhus toxicodendron or Rhus tox (RT) in alternative medicines 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, TRPA1 and TRPM3 may potentially be safer targets. Indeed, antagonists of TRPA1 and TRPM3 did not affect core body temperature in preclinical studies (Chen et al, ; Jia, Zhang, & Yu, ; Straub et al, ), and heat withdrawal latencies were only marginally altered in DKO M3/A1 mice (Vandewauw et al, ). We expect that further preclinical and clinical studies will reveal whether pharmacological modulators of these channels can be developed as novel weapons in the battle against pain.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%